The handbook of economic development and institutions - Baland, Jean-Marie; Bourguignon, François; Platteau, J. P. (Jean-Philippe), 1947-; Verdier, Thierry, 1961- (Princeton University Press, 2020)
"The essential role that institutions play in understanding economic development has long been recognized across the social sciences, including in economics. Academic and policy interest in this subject has never been higher. The Handbook of Economic Development and Institutions is the first to bring together in one single volume the most cutting-edge work in this area by the best-known international economists. The volume's editors, themselves leading scholars in the discipline, provide a comprehensive introduction, and the stellar contributors offer up-to-date analysis into institutional change and its interactions with the dynamics of economic development. This book focuses on three critical issues: the definitions of institutions in order to argue for a causal link to development, the complex interplay between formal and informal institutions, and the evolution and coevolution of institutions and their interactions with the political economy of development. Topics examined include the relationship between institutions and growth, educational systems, the role of the media, and the intersection between traditional systems of patronage and political institutions"--Publisher's description.